INOVASI PENDIDIKAN ISLAM DI ERA POST TRUTH: TANTANGAN DAN PELUANG PEMBELAJARAN PAI DI SEKOLAH UMUM TINGKAT MENENGAH - Unang Sodikin; Dedi Supriadi; Samsuddin; Maryanton Nur Shamsul (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2023)
This article aims to analyze innovations in Islamic Religious Education (PAI) learning as a response to the challenges of the post-truth era. The main focus of this study is on the integration of Islamic values with modern technology, strengthening Islamic digital literacy, and developing problem-solving and critical thinking-based learning methods. The method used in this research is a literature review that examines various relevant sources, including journal articles, books, and research reports related to Islamic education and the challenges of the post-truth era. The analysis describes the opportunities, challenges, and innovative strategies in PAI learning. The results of this study indicate that innovations in PAI learning, such as the application of e-learning, gamification, Islamic applications, and blended learning models, can enhance the relevance, attractiveness, and effectiveness of education. Furthermore, strengthening Islamic digital literacy and institutional collaboration are strategic opportunities to deliver relevant education in the digital era. However, challenges such as unequal access to technology and the spread of misinformation remain obstacles requiring sustainable solutions. This article concludes that innovations in PAI learning can equip students with critical, ethical, and adaptive skills, enabling them to face global challenges while strengthening Islamic values in the post-truth era